2012
DOI: 10.1186/2110-5820-2-s1-s21
|View full text |Cite
|
Sign up to set email alerts
|

Early continuous veno-venous haemofiltration in the management of severe acute pancreatitis complicated with intra-abdominal hypertension: retrospective review of 10 years' experience

Abstract: BackgroundConservative treatment of patients with severe acute pancreatitis (SAP) may be associated with development of intra-abdominal hypertension (IAH), deterioration of visceral perfusion and increased risk of multiple organ dysfunction. Fluid balance is essential for maintenance of adequate organ perfusion and control of the third space. Timely application of continuous veno-venous haemofiltration (CVVH) may help in balancing fluid replacement and removal of cytokines from the blood and tissue compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Systemic inflammation with increase in vascular permeability leads to exsudation with inflammatory fluid accumulation in intraabdominal and retroperitoneal cavities and increase in intraabdominal pressure with resultant intraabdominal hypertension (IAH) (ref. 20 ). Abdominal compartment syndrome (ACS) is a severe complication of SAP and is significantly associated with patient prognosis.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic inflammation with increase in vascular permeability leads to exsudation with inflammatory fluid accumulation in intraabdominal and retroperitoneal cavities and increase in intraabdominal pressure with resultant intraabdominal hypertension (IAH) (ref. 20 ). Abdominal compartment syndrome (ACS) is a severe complication of SAP and is significantly associated with patient prognosis.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Application of CVVH in 75 of studied patients resulted in faster decrease in IAP during the first phase of the disease when IAP reached 10.6±3.9 mmHg within two weeks, while the mean IAP in patients treated without CVVH was still elevated at 12.9±4.1 mmHg (ref. 20 ).…”
Section: Intraabdominal Hypertension and Abdominal Compartment Syndromentioning
confidence: 99%
“…The role of CHDF has been investigated using the polymethyl methacrylate (PMMA) membrane for the elimination of pro-inflammatory cytokines in severe AP. Pupelis et al, in a 10-year retrospective review of studies using CVVH in patients with AP, concluded that balancing the replacement of fluids and the elimination of blood cytokines resulted in a decrease in the requirement for surgical interventions from 41% to 19% [90,91]. The Japanese guidelines suggest that organ failure, but not mortality, can be prevented in severe AP.…”
Section: Other Drugsmentioning
confidence: 99%
“…However, the effect of furosemide alone has not been studied in a randomised setting in patients with IAH or ACS. In two retrospective analyses of patients with severe acute pancreatitis, application of RRT was associated with: 1) a negative cumulative fluid balance (approximately -1.8 L vs + 5.3 L on day 7, P < 0.001) [31]; 2) reduced incidence of IAH (31% to 14%, P < 0.01) and ACS (11% to 4%, P = 0.02) [32]; 3) reduced surgical requirements (41% to 19%, P < 0.001) [32]; and 4) a trend towards reduced mortality (12 vs 14%, non-significant) [31]. In a follow up study, Mullens et al studied nine patients with acute decompensated heart failure who did not respond to the initial medical (mainly furosemide based) treatment.…”
Section: Place For Furosemide Infusion or Renal Replacement Therapymentioning
confidence: 99%